The Role of Nitric Oxide in the Autoregulation of Cerebral Blood Flow and the Pathogenesis of Cerebral Vascular Spasm in Patients with Ruptured Cerebral Aneurysms - A. V. Prirodov; S. V. Zhuravel; E. Yu. Bakharev; I. I. Goncharova; P. D. Zorin; E. V. Klychnikova; E. V. Tazina; A. A. Grin; S. S. Petrikov (Неотложная медицинская помощь)
The presented literature review is devoted to the role of the endothelial relaxing factor – nitric oxide (NO) – in the regulation of cerebral blood flow in patients with ruptured intracranial aneurysms. Modern views on the physiology of NO, methods of regulation and autoregulation of its synthesis are described, experimental and clinical data on the disruption of the production of the endothelial relaxing factor in subarachnoid hemorrhage are presented.